Estudio de factibilidad para la creación de una microempresa de compra y venta de ganado bovino en pie en el cantón Quevedo - Velásquez Lucas, Eliana Rocío (2013)
This bill establishes the feasibility of creating a micro purchase and sale of live cattle in the Canton Quevedo. Consists of seven chapters: Introduction, Theoretical Framework, technical study, Organizational and Legal, Financial Study, Conclusions, Recommendations, bibliography and appendices. The first chapter describes the background that led to the completion of the project, this was done based on the problem statement, the same as with the formulation and systematization allows us to raise the goals were met with the development of this project, besides that justified the project and the viability of the hypothesis. In the second chapter presented the theoretical foundation behind the project based on specifications established by different authors in the realization of the project. We describe the most important for the development of a feasibility study are market research, technical, organizational, legal and financial. In the third chapter we studied the materials and methods which consist in: location, materials, methodology, analysis of pricing, marketing, advertising, purchase of animals, animal health, pasture management. The fourth chapter covers the results obtained by studying the market which made it possible to analyze the demand, supply and marketing, which allowed us to determine the commercial viability of the project. In the same chapter we examined the technical study which involves the location, implementation, necessary resources and processes required for the daily operation of the company, which allowed us to demonstrate the technical feasibility of the project, also studied the organizational structure which implies the company name, slogan, mission, vision, goals, values, administrative structure and legal requirements for the implementation of the company and finally analyzed the financial study that shows the initial investment of the project, projected cash flow, financial indicators, the recovery time of the investment elements that allow the investor to make decisions. The fifth, sixth and seventh conclusions, recommendations, references and annexes which includes the survey form